Take it away: the need for designing fecal sludge disposal services for single-pit latrines - Balasubramanya, Soumya; Evans, E.; Ahmed, R.; Habib, A.; Asad, N.S.M.; Rahman, M.; Hasan, M.; Dey, D.; Camargo Valero, M.A.; Rao, Krishna Chaitanya; Fernando, Sudarshana (IWA Publishing, 2017)
The government of Bangladesh is increasingly paying attention to the safe collection and disposal of fecal sludge from pit latrines in rural areas. In this paper, we report on current sludge disposal practices from single-pit latrines, by conducting a survey of 1,091 households with pit latrines in a rural subdistrict of Bangladesh. Almost all households were using their pits, and 90% reported that hiring pit emptiers to empty the pit for reuse was the dominant pit management practice. However, 90% of households also reported that the sludge from these pits would be disposed of in the vicinity of their homes, by digging wide and shallow troughs in the soil to absorb the sludge. These results indicate an urgent need to design an organized service that safely transports fecal sludge away for treatment. The National Committee for Fecal Sludge Management, constituted by the government of Bangladesh, is using these results to design policy for sludge management.